TRADISI LEBARAN KETUPAT DI KAMPUNG JAWA KOTA TOMOHON - Zulkarnaen Me’akhir Yanus Putra Hulu (HOLISTIK, Journal of Social and Culture, 2023)
Kampung Jawa is one of the villages in Tomohon City which was founded in 1875 by Muslim freedom fighters from Serang City, Banten Province. The fighters were interned by the Dutch to Minahasa because they were considered dangerous. This village they named Kampung Jawa to commemorate the land of their ancestors Java. But by the inhabitants of Tomohon it is called "Tonyawa" (Javanese). With the existence of the Javanese Village of Tomohon City, making the birth of various customs and customs or traditions. One of the annual traditions carried out by the people of Kampung Jawa Tomohon is the tradition of Eid Ketupat. This Eid ketupat tradition is carried out by the residents of Tomohon Java Village as their gratitude after fulfilling the Shawwal fast for 6 days, starting from the day after Eid al-Fitr. This Eid ketupat tradition is one of the traditions of Muslims which is carried out every year in Tomohon Java Village, where the majority of the religion of the people of Tomohon City adheres to Christianity and Katolik. Realizing that differences in cultural background and tradition are something that usually happens in the community, the people around Kampung Jawa Kota Tomohon have the view that the celebration of the Eid ketupat tradition in Kampung Jawa Tomohon is a form of real tolerance that exists between the surrounding community and Kampung Jawa Tomohon. Keywords: tradition, Javanese, Eid ketupat